Natural Gas Distribution Infrastructure and the Quest for Environmental Sustainability in the Niger Delta: The Prospect of Natural Gas Utilization in Nigeria - Agbonifo, Philip Ejoor (International Journal of Energy Economics and Policy, 2016)
Natural gas distribution infrastructure is critical to socioeconomic development and environmental sustainability in Nigeria. Environmental degradation has benefited largely from inadequate natural gas utilisation and infrastructural development in the domestic and regional networks to gather, transmit and distribute the associated gas produced. Thus, this paper explores the concept of gas development to promote sustainable development and to tackle the problem of environmental degradation in Nigeria. It identified the various natural gas utilisation projects in the domestic, regional and international networks to stimulate economic growth as well as the quest for environmental sustainability across the gamut of Nigeria. These projects enable captured gas to be harnessed for socioeconomic and environmental benefit, eliminate routine gas flaring and create the much needed gas infrastructure for development. Quite remarkably, natural gas distribution infrastructure creates undisputed domestic and regional hub gas based opportunities for industries in the domestic network. It also acts as industrial feedstock to consolidate the market share in high value export market through the liquefied natural gas (LNG), Escravos Gas Project and the West Africa Gas Pipeline (WAGP) in the West African sub region. Keywords: Natural gas utilisation; environmental sustainability; environmental preservation; JEL Classifications: O13, Q55